Tinjauan Tentang Pelaksanaan Lelang Atas Agunan Hak Tanggungan Dalam Perkara Kredit Macet (Studi Putusan Nomor 86/PDT/2015/PT.MDN) - Suhaila Zulkifli (Universitas Islam Sumatera Utara, 2018)
Banks as a financial institution when distributing credit to the public can minimize risk by applying clear and complete legal guarantees since any credit disbursement requires a guarantee of the repayment of debtor's debt if he breaches an appointment or bankrupt. Credit guarantees will provide legal certainty to the bank that the credit will remain back by the execution of the credit guarantee to reduce bad loans. The research method in this writing is the normative juridical to know the provisions on the conduct of auctions on objects of collateral in the credit agreement and to analyze the decision No. 86 / PDT / 2015 / PT-MDN. The legal provisions on the granting of collateral in the credit agreement are regulated on the laws No.4 of 1996 on mortgages, No.42 of 1999 on fiduciary guarantee and No. 10 of 1998 on Banking. The provisions on the conduct of auction on objects of collateral in the credit agreement are under Article 20, Paragraph (1) a and b, and Paragraph (2) of the Law on Mortgage Rights and Regulation of the Minister of Finance No. 106 / PMK.06 / 2013 about Auction Implementation Guide. Keywords: Auction, Collateral, Bad Loans